“I just finally wanted to belong somewhere”—Qualitative Analysis of Experiences With Posting Pictures of Self-Injury on Instagram - Brown, Rebecca C.; Fischer, Tin; Goldwich, David A.; Plener, Paul L. (Frontiers in Psychiatry, 2020)
Non-suicidal self-injury (NSSI) is a common phenomenon among adolescents, but is often not disclosed due to fear of stigmatization. Social media is frequently used to publish photos of NSSI and share experiences with NSSI. Objectives of this study were to find out more about the motivation for publishing NSSI content and to investigate the effect that sharing this content on social media has on young people. In the current study, we interviewed N=59 participants (mean age=16.7 years (SD=1.2 years); 72.9% female), who had all posted NSSI content within the past month on the social media platform Instagram. Semi-structured interviews were conducted via the Instagram messaging app. Interviews were analyzed qualitatively, assisted by the Software Atlas.ti 7. Participants were asked about their motivation for and their experiences with posting NSSI content online. Motivations for posting pictures online were mainly social (connecting, disclosure, communicating), while self-focused reasons like documenting NSSI or recovery were also mentioned. All participants reported having received positive reactions (being offered help, connecting, receiving empathy), as well as negative comments (being abused, being misunderstood) to their own NSSI content by other Instagram users. Participants’ reactions to other users’ NSSI content on Instagram was often identification with the content or being triggered, but also wanting to offer help or sometimes even being deterred from NSSI. None of the participants mentioned successful referral to professional help through their online NSSI activity. One target for future interventions could therefore be social media- or other online platforms, where adolescents might be more easily reached. Mental health practitioners should be aware of their clients’ online activity and encourage reflection upon positive and negative effects of viewing or sharing NSSI content online.